Community Health Service Implementation Through Bpjs Health Program - Hasrilah Hasrillah; Yaqub Cikusin; Hayat Hayat (SENGKUNI Journal (Social Science and Humanities Studies), 2021)
This research is the result of research that describes the implementation of BPJS Kesehatan in Kedungkandang Health Center, Malang City. The purpose of this research is to know the factors that hinder and support the implementation of the BPJS health program at the Kedungkandang Health Center, and to find out how the BPJS Kesehatan program is implemented at the Kedungkandang Health Center.This study uses several theories, namely Public Policy, Health Service Policy, Implementation. Researchers found 4 factors affecting the implementation process of the BPJS Health program at the Kedungkandang Health Center, namely first, the communication or socialization factor, while the second, the resource factor, from human resources to other resources such as facilities, information, then third, dispotition factors. or the attitude of the bureaucratic apparatus, and fourth, the bureaucratic structure factor. The research method used is qualitative. The research was conducted in the city of Malang, the place is in the Kedungkandang Health Center, the Health Office. Data collection techniques in this study were observation, interviews, and documentation. From research conducted based on field studies in the form of observations and interviews, researchers found that the implementation process at the Kedungkandang Health Center was running quite well, although there were still some obstacles, the Kedungkandang Health Center and the Health Office continued to fix the deficiencies in the process. the implementation of the BPJS program can run well. Based on the research can conclusion The BPJS program is a form of bureaucratic reform in the health sector, because with the BPJS program the community can get treatment more easily and it is not difficult to file documents like the previous health system. With the existence of the BPJS program, it is hoped that it can improve the quality and quality of health service providers to the community in Malang City.